Population of the Łódź Voivodeship: development and structural transformations - Dzieciuchowicz, Jerzy (Acta Geographica Lodziensia, 2019)
The subject of this study was the development and structural transformation of the population of the Łódź Voivodeship over the last more than one hundred years. Population transformations were analysed for four periods: 1) pre-1918; 2) 1918–1945; 3) 1946–1989; and 4) 1990–2018. A demographic forecast of the Łódź Voivodeship was made up to 2050. The structure of the population of the investigated region was considered, taking into consideration the population according to demographic, socio-economic and socio-cultural divisions and spatial features. The basic aim of the author was to establish general tendencies in the development and restructuring of the population of the Łódź region and its spatial typology.